POPULATION DYNAMICS OF THE GRAY EEL CATFISH Plotosus canius FROM PORT DICKSON, MALAYSIA - Usman, Binta Isyaku; Moruf, Rasheed Olatunji; Amin, S. M. Nurul; Arshad, Aziz (Jakarta Technical University of Fisheries, 2024)
Given the scarcity of information suitable for stock assessments of the Plotosidae, the study on growth and population dynamics of the Gray Eel Catfish Plotosus canius from the coastal waters of Port Dickson, Peninsular Malaysia was carried between January and December, 2021 and estimated using the ELEFAN I routine in FiSAT software. Estimated von Bertalanffy growth parameters were asymptotic length (L∞) = 67.20 cm, growth coefficient (K) = 0.95 yr-1, Predicted extreme length (Lmax) = 63.54, and growth performance index (φ’) = 3.63. The estimated total mortality (Z) value was 2.73 yr-1 during the study period. Natural mortality (M) and fishing mortality (F) were estimated at 1.31 yr-1 and 1.42 yr-1 respectively. The value of exploitation rate (E) obtained for P. canius was 0.48. Two major recruitment events were observed per year and the recruitment pattern was continuous. The findings from the analyses suggested that the P. canius fishery in the study area is slightly below the optimum level of exploitation. However, more research is suggested in such direction to corroborate the present findings as management for this fish is indispensable for maximum sustainable yield. The length-structured virtual population analysis revealed that P. canius fishery of Port Dickson experiences growth overfishing as opposed to recruitment overfishing, with fishing mortality being higher than natural mortality (F>M). Based on these findings, small-sized mesh fishing net and reduced fishing efforts (legal and illicit) must be enforced in order to maintain the potential of this commercially significant species in Port Dickson, Malaysia